Urban soil pollution in Turkiye: a review of potentially toxic elements, polycyclic aromatic hydrocarbons, and microplastics in major cities - Cayir, Gulfem; Rouhani, Abdulmannan; Al Souki, Karim Suhail; Blazalek, Lidia; Newton, Robert Ato; Sukur, Fatma Zehra; Pidlisnyuk, Valentina (SPRINGER, 2025)
Rapid urban development and industrialization have led to severe soil pollution, which has become a major global environmental problem, further intensified by population growth and land-use changes. In urban soils, pollution from past anthropogenic activities can still be detected through its harmful effects on soil quality, ecosystems and human health. This review summarizes the status of potentially toxic elements (PTEs), polycyclic aromatic hydrocarbons (PAHs), and microplastics (MPs) in Turkiye's urban soils. Across cities, Cd and Pb frequently exceeded national soil-quality thresholds, with industrial hubs and traffic corridors emerging as hotspots. PAH burdens often reached the 'heavily contaminated' category (> 1000 mu g kg(-)(1)), with winter maxima linked to heating activities and a dominance of pyrogenic four-ring compounds. Urban MPs were abundant in parks and along roadsides, dominated by fibers and polyethylene, and showed strong variation with land use (recreational > industrial > residential in & Idot;stanbul). This evidence illustrates a lack of in-depth understanding of the full extent of soil pollution in targeted areas. The results of this review will help develop practical strategies for soil management, pollution monitoring, and remediation, which will ultimately improve public health and support sustainable development in Turkiye.
Keywords: Urban soil contamination; Anthropogenic activities; Pollution monitoring; Urbanization; Turkiye; HEAVY-METAL CONTAMINATION; INDUSTRIAL-AREA; TRACE-ELEMENTS; ROADSIDE SOIL; SURFACE SOIL; PAHS; PCBS; REGION; DEPOSITION; ISTANBUL; Environmental Sciences & Ecology